2005
DOI: 10.1007/s10773-005-4436-0
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Quasi-Exactly Solvable Models

Abstract: Various quasi-exact solvability conditions, involving the parameters of the periodic associated Lamé potential, are shown to emerge naturally in the quantum Hamilton-Jacobi approach. It is found that, the intrinsic nonlinearity of the Riccati type quantum Hamilton-Jacobi equation is primarily responsible for the surprisingly large number of allowed solvability conditions in the associated Lamé case. We also study the singularity structure of the quantum momentum function, which yields the band edge eigenvalues… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In section 3 we will apply the supersymmetry transformations for generating new periodic and asymptotically periodic potentials which are almost isospectral to the initial associated Lamé potential. In section 4 our general results will be illustrated through the particular case characterized by (m, ℓ) = (3,2). Our conclusions will be finally given at section 5.…”
Section: Introductionmentioning
confidence: 91%
“…In section 3 we will apply the supersymmetry transformations for generating new periodic and asymptotically periodic potentials which are almost isospectral to the initial associated Lamé potential. In section 4 our general results will be illustrated through the particular case characterized by (m, ℓ) = (3,2). Our conclusions will be finally given at section 5.…”
Section: Introductionmentioning
confidence: 91%
“…x−x k is sum of the moving pole terms [26][27][28][29][30][31][32][33] that can be expressed as P (x)…”
Section: The Modelmentioning
confidence: 99%
“…On the other hand, quantum Hamilton-Jacobi (QHJ) formalism has generated much interest [22,24,25]. The application of QHJ to eigenvalues has been explored in great detail by Bhalla, Kapoor and collaborators [26][27][28][29][30][31][32][33]. QES systems have been also studied within QHJ approach [31].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the singularity structure information has provided interesting insights into the models studied. It has been shown that, the singularity structure of the QMF is markedly different, for the exactly solvable (ES) [6], [7], quasi-exactly solvable (QES) [8], [5], periodic potentials [9], [10] and the new rational potentials, with exceptional polynomials as solutions [11]- [13]. For supersymmetric one dimensional ES potentials [14], [15], the singularity structure of the QMF provided a link to the exactness of the SWKB integral [13], [16].…”
Section: Introductionmentioning
confidence: 99%